(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the scope of use of compound nouns, the features of their formation are analyzed in detail. Also, in the written sources of the 19th century ("Mirzoolim Mushrif’s work "History of the Koqan Khanate"), there is an opinion about the semantic groups of nouns.